Reflecting Light : When light hits the fan. (Gent : KASK School of Arts, 2022)
Csornai, Emese ; Doublier, Henri Emmanuel ; Fedinger, Jan ; Humalisto, Tomi ; Maertens, Jan ; Pocheron, Bruno ; Veldhuis, Ezra ; Coeman, Bram ; Belpaeme, Geert
"Reflecting Light is a fanzine, a fan magazine for those who, like us, are admirers of light. Who are we? We are a group of lighting designers, working internationally in the performing arts, who collaborate on a research project at KASK School of Arts Ghent. Our research concerns - as you might have guessed - light."
boek